Specific immune response to M. tuberculosis and ability to in vitro control mycobacterial replication are not impaired in subjects with immune-mediated inflammatory disease and tuberculosis infection - Farroni, Chiara; Altera, Anna Maria Gerarda; Salmi, Andrea; Vanini, Valentina; Cuzzi, Gilda; Lindestam Arlehamn, Cecilia S.; Sette, Alessandro; Delogu, Giovanni; Palucci, Ivana; Sbarra, Settimia; Aiello, Alessandra; Picchianti-Diamanti, Andrea; et al. (Frontiers in Immunology, 2025)
BackgroundSubjects with immune-mediated inflammatory diseases (IMID), such as rheumatoid arthritis, with tuberculosis infection (TBI), have a high probability of progressing to tuberculosis disease (TB). We aim to characterize the impact of IMID on the immune response to M. tuberculosis (Mtb) in patients with TBI and TB disease.MethodsWe enrolled TBI and TB patients with and without IMID. Peripheral blood mononuclear cells (PBMCs) were stimulated with Mtb-derived epitopes (MTB300). By flow-cytometry, we identified the Mtb-specific CD4+ T cells as cytokine-producing T cells or as CD25+ CD134+ CD4+ T cells. Memory and activation status of Mtb-specific T cells were assessed by evaluating: CD153, HLA-DR, CD45RA, CD27. Mycobacterial growth inhibition assay (MGIA) was used to evaluate the ability of PBMCs to inhibit mycobacteria growth. A long-term stimulation assay was used to detect a memory response.ResultsThe IMID status and therapy did not affect the magnitude of response to Mtb-antigen stimulation and the number of responders. TBI-IMID showed a cytokine profile like TBI and TB patients. The Mtb response of TBI-IMID patients was characterized by an effector memory and central memory phenotype as in TBI and TB groups. This memory phenotype allowed the increased IFN-γ production after 6 days of MTB300-stimulation. HLA-DR expression on Mtb-specific T cells was associated with TB, whereas CD153 was associated with TBI status. Finally, the TBI-IMID had an MGIA response like TBI and TB patients.ConclusionIMID condition does not affect key aspects of the immune response to Mtb, such as the cytokine response, memory and activation profile, and the ability to contain the mycobacteria replication. The immunological characterization of the fragile population of TBI-IMID patients is fundamental to understanding the correlation between protection and disease.